DAYA TERIMA DAN KANDUNGAN PROTEIN SERTA ZAT BESI ABON IKAN TUNA (Thunnus sp.) DENGAN PENAMBAHAN DAUN KATUK (Sauropus androgynus): Acceptability and Protein and Iron Content of Shredded Tuna (Thunnus Sp.) with The Addition of Katuk Leaves (Sauropus Androgynus). - Masud, Hikmawati; Nursalim, Nursalim; Tory, Rini Dwikurniati (Media Gizi Pangan, 2024)
Abon tuna fish as a product developed to increase nutritional value, especially iron, requires the addition of vegetables such as katuk leaves. Katuk leaves are known as breast milk facilitating vegetables. In addition, katuk leaves are also iron-rich vegetables to prevent anemia because the mineral content in katuk leaves is quite high, especially Fe which can be used to prevent fatigue due to anemia. This study aims to determine the acceptability and protein and iron content of shredded tuna fish (Thunnus sp.) with the addition of katuk leaves (Sauropus androgynus). This research method is pre-experimental research with a post test group design approach. In this study, shredded tuna fish products were developed with the addition of katuk leaves with three treatment concentrations of 15%, 20% and 25%. This research was conducted in January - February 2023 at the Organoleptic Test Laboratory of the Nutrition Department of the Makassar Poltekkes Kemenkes with 30 untrained panelists. Analysis of protein and iron content using Micro Kjeldahl and AAS (Atomic Absorption Spectrophotometry) methods. The results of the acceptability test were carried out using the Kruskall wallis test and continued with the Mann Whitney test. In the liking test, the most preferred color, aroma and taste were F1, the most preferred texture was F2. The highest protein content in F1 amounted to 39.72 g/100 g and iron in F3 amounted to 4.74 mg/100 g. Further studies need to be conducted on the utilization of shredded products